Psikologi Positif Melalui Humor dalam Menumbuhkan Kesehatan Mental - Syadiyah, Reghifa Khalimatus; Astuti, Risma Hesti Yuni; Aprilliani, Firna (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2021)
In this era, technology is developing rapidly. Technological developments have a good impact but also have a bad impact on users. A good impact will certainly bring benefits to its users while a bad impact will bring problems. This can lead to problems related to mental health. Various pressures can trigger problems that can lead to stress, worry, sadness, moodiness, lack of enthusiasm, frustration to despair. In situations like this, positive emotions are needed to help relieve the pressure that is felt. One of the positive psychology that can be done is through humor. Humor can be both good and bad emotions. Humor is said to be bad done in excess so that it hurts the person concerned. Conversely, good humor will provide a sense of relaxation and calm for the person. Many people have the notion that humor is just a light joke that causes a sense of pleasure to release happy laughter. But it turns out that humor has a great function in it. Research conducted, that humor has an important role in mental health. Positive psychology of humor helps a person to reduce stress in his mind and heart so that it can help his problems. Research conducted on adolescents shows that a lot of stress is experienced by students. This proves that humor can be a coping mechanism for adolescents. In this study, the researcher used a descriptive qualitative method which aims to test the effectiveness of humor in helping to grow mental health and helping facilitate problem solving